Determinasi Keputusan Pembelian Generasi Z pada TikTok Shop melalui Online Customer Rating, Online Customer Review, dan Voucher Gratis Ongkir - Ainur Rohma; Luluk Nur Azizah; Diah Ayu Novitasari (Commodities, Journal of Economic and Business, 2026)
This study aims to analyze the influence of online customer rating, online customer review, and free shipping vouchers on purchasing decisions in the TikTok Shop application among Generation Z consumers in Turi District, Lamongan Regency. This research employed a quantitative approach using a survey method. The sampling technique used was purposive sampling with a total of 387 TikTok Shop users as respondents. Data were collected through questionnaires and analyzed using multiple linear regression analysis with the assistance of SPSS version 20. Data testing included validity, reliability, classical assumption, t-test, F-test, and coefficient of determination tests. The results showed that partially, online customer rating, online customer review, and free shipping vouchers had a positive and significant effect on purchasing decisions. Simultaneously, the three variables also significantly influenced purchasing decisions on TikTok Shop. The most dominant variable affecting purchasing decisions was online customer review. This study indicates that customer reviews, product ratings, and free shipping promotions are important factors in increasing consumer purchasing decisions, especially among Generation Z consumers on social commerce platforms.